The eager fight for supremacy in the online service industry: a comparative study of M&A activities: case studies of Apple, Google and Microsoft - Roder, Marius Johannes (2015)
The Online Service Industry is characterized by high M&A activity in the time from 2005 to 2015. Especially the leading companies Apple, Google and Microsoft embed this way of inorganic growth in their corporate strategy. The thesis examines the M&A activities of these major players. Therefore, it addresses two different aspects: First, it intends to do a step towards closing a research gap in literature. This gap is constituted by a missing link in the current state of literature between the corporate strategy of these firms and the choice of their M&A targets. Second, it aims to give estimation about potential future developments in the sector. Through a qualitative content analysis of companies’ publications, market research reports and other third party content, case studies are being developed. Findings show the process of strategic positioning for Apple, Google and Microsoft within the Online Service Industry between 2005 and 2015. The ongoing M&As are being analyzed regarding the companies’ corporate strategies and their strategic responsiveness regarding their direct competitors. Findings give evidence for aggressive M&A activities in the strategic groups the companies share with each other, especially in the market for mobile communication devices and communication services.